Sweden’s Fifteen Years of Communication Efforts - Boado-Penas, María del Carmen; Settergren, Ole; Ekheden, Erland; Naka, Poontavika (World Bank, Washington, DC, 2019)
It is desirable that pension reforms and legislated rules have the backing of thepopulation or at least are accepted by voters. With the objective of achieving “acceptance,”the Swedish Pensions Agency publishes an annual actuarial balance of the solvency of the whole public pension system and distributes to each participant information on his or her individual accumulated notional balance and funded accounts, movements during the year,and estimates of the projected individual future pension amount. This paper describes the Swedish pension experience in communication with pension participants over the last decade, together with the main changes in information delivered to improve individuals’ pension knowledge and help them make more informed, better decisions on work, savings,and retirement.